Peningkatan Tata Kelola Organisasi Dengan Penganganan Tata Naskah Dinas Politeknik Harapan Bersama Tegal - Ratri Wikaningtyas; Ghea Dwi Rahmadiane; Bahri Kamal (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This community service aims to improve organizational governance at Politeknik Harapan Bersama through the handling of official manuscripts. A community service approach is used to involve internal stakeholders of Politeknik Harapan Bersama in the process of improving organizational governance. This service involves the development of more effective official manuscript guidelines, training for administrative staff regarding the implementation of these guidelines, as well as assistance in the implementation and evaluation process. The results showed an improvement in administrative efficiency, accountability, and transparency in the organizational governance process at Politeknik Harapan Bersama. The positive impacts of this service include reduced administrative workload, increased compliance with applicable regulations, and increased employee satisfaction regarding administrative processes. In addition, external parties also experience increased comfort and speed in getting services from Politeknik Harapan Bersama. This service makes a real contribution to efforts to improve organizational governance in educational institutions. The practical implication is that there is a better understanding of the importance of official manuscripts in supporting the efficiency and transparency of administrative processes in higher education institutions.